Peningkatan Efektivitas Penilaian Prestasi Kerja dalam Konteks Organisasi Modern - Ajuj, Sausan Syarifatul; Fardani, Laelly Kusuma Ayu; Wardani, Yuniar; Anggraeni, Dwi Putri (As-Syirkah: Islamic Economic & Financial Journal, 2024)
Job achievement assessments are a central element in the management of human resources that have a significant impact on the performance of individuals and organizations as a whole. In an effort to further study the performance assessment practice in the context of modern organizations, this study has taken a deep look at the findings of the five international journals regarding job achievement assessments. Our analysis opened up insights into a significant trend change in the achievement assessment approach, gave valuable insights into its practical implications, and provided a number of strategic Suggestions that could be used to improve the effectiveness of job achievement assessments in various types of organizations. The findings of this study offer a deeper understanding of how achievement assessments of work can be a more effective tool in achieving organizational goals and managing human resources more efficiently.